The apostolic defence of the Gospel : Christian apologetic inthe New Testament - Bruce, F.F., (Frederick Fyvie), 1910-1990 (London, UK : IVF, 1959)
Includes bibliographial references.
Contains five lectures delivered in April 1958, at Calvin College and Seminary, Grand Rapids, MI, Princeton Theological Seminary, NJ, and Western Theological Seminary, Holland, MI.
Keywords: Bible. N.T. -- apologetics -- history -- Early church, ca. 70-300.